Integrated Sachs-Wolfe effect in massive bigravity - Enander, Jonas; Akrami, Yashar; Mörtsell, Edvard; Renneby, Malin; Solomon, Adam R. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We study the integrated Sachs-Wolfe (ISW) effect in ghost-free, massive bigravity. We focus on the infinite-branch bigravity (IBB) model which exhibits viable cosmic expansion histories and stable linear perturbations, while the cosmological constant is set to zero and the late-time accelerated expansion of the Universe is due solely to the gravitational interaction terms. The ISW contribution to the CMB auto-correlation power spectrum is predicted, as well as the cross-correlation between the CMB temperature anisotropies and large-scale structure. We use ISW amplitudes as inferred from the WMAP 9-year temperature data together with galaxy and AGN data provided by the WISE mission in order to compare the theoretical predictions to the observations. The ISW amplitudes in IBB are found to be larger than the corresponding ones in the standard ΛCDM model by roughly a factor of 1.5, but are still consistent with the observations.
Gesehen am 13.07.2020